Income, consumption, and saving nexus of jaffna tamil households: is there a lesson to build back better? - Karunaanithy, K. (University of Jaffna, 2022)
Purpose:With an objective to find out the ways and means to build back better from the present crisis and to document quantifiable consumption (Vs. Saving) behavior of Tamil households at the district level, this study distills lessons from the past consumption behaviour and the spending dynamics that are vital for recovery policy formulation. Methodology: This cross-sectional mixed method study, documents the nuances in income, consumption, and saving during the pre-pandemic period, with 500 households from all DS divisions of the Jaffna district; it covered five job groups (permanent salary holders, businessmen, fisher folks, farmers, and wage-earners) proportionately via three stages (District, DS Division, and GN divisions) stratified random sampling method. Questionnaires and short interviews were used to collect primary data under a survey method that addressed the research question, 'how and to what extent consumption behaviour (Vs. saving) varies across different job groups, income levels, and regions'. Findings: By employing central tendency measures, cross-tabulation, ratio statistics, and local regression (LOESS), the Findings suggest consumption expenditure has strong negative influence on saving behavior and creates challenges to building back better due to income inequality and poverty; the consumption pattern is not uniform across households- APC (consumption/ income ratio) shows an average of 0.64, but varies across jobs (ranging from 0.57 to 0.81); income levels (ranging from 1.49 to 0.1); regions (lowest 0.59 highest 0.77); the share of food and nonfood expenditure of income also vary across jobs (highest among wage earners i.e. 40 and 33 percent respectively); fitted LOESS curves also indicate the negative influence of consumption on willingness to save (saving ratio), but moderated by income level and demographics. The results attest that the prevalence of wider disparities across households, which is not so far documented quantitatively in this region. Research limitation: The study acknowledges the multi-dimensional nature of saving and emphasises the need for longitudinal studies to distinguish trends. Implications: places new information on the conditioning effect of consumption expenditure on income and saving; the efforts to control, regulate, and restructure consumption to transfer income into saving would get better clarity; based on lessons from regional, job, income differences, and the cultural roots of Tamils, fair recovery policies at the micro-level be designed in a participatory manner to build back better. Economic revival measures under the present crisis could benefit from these Findings by acknowledging the micro differences at the household level.
Keywords: Consumption; Household income; Job categories; Regional variation; Savings